The Radiological Evaluation of Mandibular Canal Related Variables in Mandibular Third Molar Region: a Retrospective Multicenter Study - Dogukan Yilmaz; Emel Tuğba Ataman-Duruel; Zehra Beycioğlu; Samir Goyushov; Tansu Çimen; Onurcem Duruel; Tolga Fikret Tözüm (eJournal of Oral Maxillofacial Research, 2022)
Objectives: The aim of this retrospective study was to investigate anatomical structure of mandibular canal and the factors those increase the possibility of inferior alveolar nerve damage in mandibular third molar region of Turkish population.